Hakikat dan Majas dalam Qawa'id Tafsir - Mangka, Jahada (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2017)
The discourse of hakikat and majaz has always been the subject of study related to various disciplines, especially Arabic and the study of the Qur'an, which is still intense to discuss. In the Qur'an, there is a considerable number of verses containing lafadz majaz, with various forms and meanings. This can be seen in the reviewing of the verse texts from various aspects of language and tafsir (interpretation). This occurs due to several indicators that can inﬂuence the shift of a lafadz from its hakikat (literal) meaning to the meaning of majaz (metaphorical). Its diﬀerences from hakikat have been discussed by the scholars in which the diﬀerences refer to a point of its use. The result of the study will be able to contribute in the understanding of the diﬀerences of both hakikat and majaz especially in the Qur’aninterpretation discipline.